Reply to Henriksen, S.; Rinaldo, C.H. Should SVGp12 Be Used for JC Polyomavirus Studies? Comment on “Prezioso et al. COS-7 and SVGp12 Cellular Models to Study JCPyV Replication and MicroRNA Expression after Infection with Archetypal and Rearranged-NCCR Viral Strains. Viruses 2022, 14, 2070” - Carla Prezioso; Ugo Moens; Valeria Pietropaolo (Viruses, 2022)
In relation to the comment by Henriksen and Rinaldo, the authors intend to emphasize that before every experiment with SVGp12 cells they routinely test the cells for the absence of BKPyV contamination. The scientists can state that the SVGp12 cells used in their laboratory were not infected by BKPyV and that their results were also validated on the COS-7 cell line, which is permissive for JCPyV infection. Therefore, the overall findings of the study and its conclusions remain authentic. The authors recommend the necessity of carefully testing SVGp12 cells for BKPyV infection before use or, alternatively, in case of a first purchase; moreover, it is possible to choose different cell lines to avoid running into this unpleasant situation.